Endocuff Vision improves adenoma detection rate in a large screening-related cohort - Forbes, Nauzer; Hilsden, Robert J.; Ruan, Yibing; Poirier, Abbey E.; O’Sullivan, Dylan E.; Craig, Kyla M.; Kerrison, Diana; Brenner, Darren R.; Heitman, Steven J. (Endoscopy International Open, 2021)
Background and study aims Endocuff Vision (ECV) increases adenoma detection rate (ADR) in randomized clinical trials; however, observational effectiveness data are lacking. We evaluated the effectiveness, safety, and practical aspects of ECV use in a large screening-related real-world cohort.Patients and methods In this observational study, patients undergoing screening-related colonoscopy from November 2018 to April 2019 comprised the baseline period, and those undergoing it from June to November 2019 comprised the ECV period, where ECV use was discretionary. The primary outcome was ADR, compared: 1) between ECV use and standard colonoscopy across both periods; and 2) between time periods. Secondary outcomes included indication-specific ADR, sessile serrated ADR (SSADR), cecal intubation rate (CIR), procedure times, patient comfort scores, and sedation use. Multilevel logistic regression was performed, yielding adjusted odds ratios (AOR) with 95 % confidence intervals (CIs).Results In 15,814 colonoscopies across both time periods, ADR was 46.7 % with standard colonoscopy and 54.6 % when ECV was used (P < 0.001). Endoscopists used ECV in 77.6 % of procedures in the ECV period, during which overall ADR rose to 53.2 % compared to 46.3 % in the baseline period (P < 0.001). ECV use was significantly associated with higher ADR (AOR 1.24, 95 % CI 1.10 to 1.40) after adjusting for relevant covariates including time period. ECV use did not result in lower CIR, longer procedure time, increased sedation use, or poorer comfort scores.Conclusions ECV use is associated with improved ADR without negatively impacting other key procedure and patient-related factors. Future studies should evaluate the cost-effectiveness of incorporating ECV into routine screening-related practice.